How to think about people who don't want to be studied: Further reflections on studying up. (September 2021) - Souleles, Daniel
It is now routine for anthropologists to study those who exercise power and control wealth and status in any number of societies. Implicit in anthropology's long-standing commitment to apprehending societies in their totality, and explicit in the call to study up, paying attention to power is just one of the routine things that anthropologists do in the course of their fieldwork. That said, many theoretical and ethical norms in the discipline are calibrated to allow researchers to both know about and protect those with relatively little power who made up much of anthropology's original topical area of interests. By contrast, studying people who exercise power entails special ethical and theoretical consideration. This article enumerates some of those considerations, and suggests that anthropologists need to have coherent theories of social action in addition to theories of social meaning. The article also suggests that some canonical disciplinary ethical norms are inappropriate for the study of the powerful for empirical and practical reasons.